Sport-specific physiological adaptations in highly trained endurance athletes - Lundgren, K. M.; Karlsen, T.; Sandbakk, O.; James, P. E. M; Tonna, A. E. (Medicine & Science in Sports & Exercise, 2015)
Purpose: This study aims to compare maximal oxygen uptake (V.O2max), blood volume (BV), hemoglobin mass (Hbmass), and brachial endothelial function, measured as flow-mediated dilatation (FMD), in international-level endurance athletes primarily exercising with the whole body (cross-country skiing), lower body (orienteering), or upper body (flatwater kayak).